Functionalizing Graphene and Carbon Nanotubes A Review /: A Review. (2016) - Ferreira, Filipe Vargas; Cividanes, Luciana De Simone; Brito, Felipe Sales; Menezes, Beatriz Rossi Canuto de; Franceschi, Wesley; Nunes Simonetti, Evelyn Alves; Thim, Gilmar Patrocínio
No abstract available